A MONUMENTAL MID-REPUBLICAN BUILDING COMPLEX AT GABII. (9th January 2018) - Johnston, Andrew C.; Mogetta, Marcello; Banducci, Laura; Opitz, Rachel; Gallone, Anna; Farr, Jason; Casagrande Cicci, Emanuele; Terrenato, Nicola
Abstract : Excavations at the Latin city of Gabii in 2012–15 conducted by the Gabii Project have uncovered a monumental building complex, hitherto known only very partially from previous excavations in the 1990s. Organized on a series of three artificial terraces that regularized the slope of the volcanic terrain, it measures some 60 m by 35 m, occupying an entire city-block. It is prominently situated at one of the most central locations within the city, on the main urban thoroughfare at the important intersection of the roads from Tibur, Praeneste and Rome. Stratigraphic evidence and construction techniques date the original phase of the building to the mid-third century BC. This report focuses on a contextualization and description of this first, mid-Republican phase and offers a preliminary interpretation of this complex as a public building, with spaces designed for a variety of functions: bathing, public feasting, and ritual activity. If this is correct, it now represents one of the very few examples of public buildings other than temples and fortifications known from the mid-Republican period, and sheds important light on the development of Roman architecture and of the Latin cities in a crucial and obscure period. Abstract : Le indagini di scavo condotte dal Gabii Project nella città latina di Gabii nel 2012–2015 hanno messo in luce un complesso edilizio monumentale, noto solo in parte da precedenti ricerche effettuate negli anni '90. L'edificio, organizzato su tre terrazze digradanti che regolarizzano il pendio del cratere vulcanico su cui sorge la città, misura circa 60 × 35 m, occupando un intero isolato. La fronte si affaccia sul principale asse del reticolo stradale in un punto nevralgico dell'impianto urbano, all'incrocio delle vie provenienti da Roma, Tibur e Praeneste. Dati stratigrafici e techniche costruttive permettono di datare la fase originaria del complesso ai decenni centrali del III secolo a.C. Il presente studio si concentra sulla contestualizzazione della fase edilizia di età medio-repubblicana, ed offre un'interpretazione preliminare del complesso come edificio pubblico, con spazi appositamente concepiti per avere diverse funzioni – bagni, banchetti, e attività rituali. Allo stato attuale delle conoscenze, esso rappresenta uno dei rari esempi di monumenti pubblici databili ad età medio-repubblicana che non siano templi o fortificazioni, fornendo importanti spunti di riflessione sullo sviluppo dell'architettura romana e delle città latine in un periodo cruciale ma ancora oscuro.